2001
DOI: 10.1136/adc.85.6.497
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of references in paediatric journals

Abstract: We analysed the reference error rate of four paediatric journals. The overall rate was 29.7%. Individual rates were as follows: Acta Paediatr 36%, Arch Dis Child 22%, J Pediatr 29%, Pediatrics 32%; the rate of major errors was 1%, 1%, 2%, and 4%, respectively. (Arch Dis Child 2001;85:497-498)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Furthermore, it gives credit to the original researchers and allows readers to easily retrieve cited articles should they want to read more widely about a particular subject [2]. Accurate references in research studies are essential for the transmission of scientific knowledge so it is imperative that they should be written properly to make searching easy [3]. Inaccuracy of references citations in the published medical literature is an ongoing problem that has been identified in a variety of specialist medical journals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it gives credit to the original researchers and allows readers to easily retrieve cited articles should they want to read more widely about a particular subject [2]. Accurate references in research studies are essential for the transmission of scientific knowledge so it is imperative that they should be written properly to make searching easy [3]. Inaccuracy of references citations in the published medical literature is an ongoing problem that has been identified in a variety of specialist medical journals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by [10], [8] and [26] found that the accuracy references in published medical journals (general and specialty) range from 3% to 60%. Another study conducted by [9] on 150 citations on the citation errors and quotation errors in the three major surgical journals and their research results shows that the citation and the quoted errors 36% and 27% respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[2], [6], [20], [22], [23], [24] and [26] stated that the majority of the errors affect the names of the authors as well as the errors in the title of the reference. A study conducted by [5] and their research results indicated from the ophthalmic literature that the error rate was ranged from the 0 to 35% and the overall error rate of the 16%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One common mistake is to cite papers that are devoid of the original information, but have used the original information of others to develop their own arguments [1]. A number of researchers pointed out that the rates of citation and quotation errors are unacceptably high in journals, which significantly diminishes the value of the reference list [2][3][4]. It has been strongly urged that the peer review of citation and quotation accuracy should be strengthened [5].…”
mentioning
confidence: 99%